Ronda clínica y epidemiológica. Introducción al análisis multivariable (parte II) (2015)
ABSTRACT: In the first part of this topic, we explained the definition of multivariable analysis, its main uses, and the three most commonly used methods in the scientific literature. In this second part, we will delve into the inclusion criteria of independent variables to the analysis, the tools to assess how the model fits the data and the interpretation of the results and coefficients in each regression model.